810. Resistance to the Minocycline-Rifampin-Chlorhexidine (MRCH) combination does not emerge in biofilms of Tetracycline and Rifampin resistant bacteria grown on MRCH catheters depleted below antimicrobially effective concentrations. (31st December 2020) - Gerges, Bahgat; Rosenblatt, Joel; Truong, Y-Lan; Reitzel, Ruth; Hachem, Ray Y; Raad, Issam I; Raad, Issam I
Abstract: Background: Central Line Associated Bloodstream Infections (CLABSIs) remain a significant medical problem for critically ill cancer patients who required catheters for extended durations. Minocycline (M) -Rifampin (R) loaded catheters have shown the greatest impact on reducing CLABSIs; however, there is a risk for developing antibiotic resistant organisms when exposed to catheters whose concentration becomes depleted below antimicrobially effective levels due to extended indwells. Chlorhexidine (CH) and M-R combination catheters (MRCH) have been proposed as a next generation catheter with improved performance. Here we studied whether bacteria that were Tetracycline and Rifampin resistant became resistant to MRCH when allowed to form biofilms on MRCH catheters depleted below antimicrobially effective MRCH concentrations. Methods: Minimum inhibitory concentrations (MICs) of Tetracycline and/or Rifampin resistant stock isolates were measured by standard microbroth dilution methods. MRCH catheters were depleted to below antimicrobially effective concentrations by soaking in serum for 6 weeks. The resistant bacteria were then allowed to form biofilm for 24 hrs on the depleted catheters in broth. Following 24 hour incubation the adherent (breakthrough) bacteria were removed by sonication and MICs were remeasured. The same organisms grown on non-antimicrobial catheters were used as controls. Results: MICs (ug/mL) of the organisms against each agent and the combination are tabulated below: MICs (ug/mL) of the organisms against each agent and the combination Conclusion: The M and R resistant bacteria did not develop in vitro resistance to the MRCH combination after forming biofilms on MRCH catheters depleted below antimicrobially effective concentrations. Disclosures: Joel Rosenblatt, PhD, Cook Medical (Shareholder, Other Financial or Material Support, Inventor of the MRCH catheter technology which is owned by the University of Texas MD Anderson Cancer Center and has been licensed to Cook Medical)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Inventor of the MRCH catheter technology which is owned by the University of Texas MD Anderson Cancer Center and has been licensed to Cook Medical) Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)